English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
0

Solve the system by using the substitution method.
x – y = –3
x – y = 4

2007-04-03 11:56:31 · 5 answers · asked by dine 1 in Science & Mathematics Mathematics

5 answers

x -y = 4 therefore y = 4-x

x-(4-x) = -3

2x-4 = -3

x = 1/2

y = 4.5

2007-04-03 11:59:45 · answer #1 · answered by Anonymous · 0 0

The second eqn yields
x = y+4
Substituting into the first eqn, we get
y+4-y = -3,
4 = -3.
So no solution!
The eqns are inconsistent.

2007-04-03 19:09:40 · answer #2 · answered by steiner1745 7 · 0 0

x-y=x-y which should mean
-3=4
so this problem doesnt work
did u do it right?

2007-04-03 19:12:18 · answer #3 · answered by Anonymous · 0 0

check the question

2007-04-03 18:59:20 · answer #4 · answered by Gladiator 2 · 0 0

you must be really stupid whats x and y?

2007-04-03 18:59:37 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers